Welcome to beach town : a novel [compact disc, unabridged] - Wiggs, Susan (Harper Audio, 2023)
In idyllic Alara Cove, a California beach town known for its sunny charm and chill surfer vibe, it's graduation day at the elite Thornton Academy. At Thornton, the students are the worldly and overindulged children who live in gated enclaves with spectacular views. But the class valedictorian is Nikki Graziola, a surfer's daughter who is there on scholarship. To the shock of everyone in the audience, Nikki veers off script while giving her commencement address and reveals a secret that breaks open the whole community. As her truth explodes into the light, Alara Cove will face a reckoning. Nikki Graziola's accusation shakes the foundation of Alara Cove, pitting her against the wealthy family whose money runs the town. Her new notoriety sends Nikki into exile for years, where she finds fame, but not fortune, overseas as a competition surfer...until a personal tragedy compels her to return to Alara Cove. As Nikki struggles to rebuild her future, she finds that the people of the town have not forgotten her. But time has changed Alara Cove, and old friendships, rivalries, and an unexpected romance draw her back into the life of the beach town she's never quite forgotten, and where joy and redemption may be possible after all.